2002
DOI: 10.2337/diabetes.51.2007.s443
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Receptor Activation Antagonizes Voltage-Dependent Repolarizing K+ Currents in β-Cells

Abstract: ؊8mol/l) in rat ␤-cells antagonized K V currents by 43.3 ؎ 6.3%, whereas the GLP-1 receptor antagonist exendin 9-39 had no effect. The effect of GLP-1 receptor activation on K V currents could be replicated (current reduction of 55.7 ؎

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 22 publications
6
79
1
1
Order By: Relevance
“…Inclusion of the non-hydrolyzable GTP-analogue GMP-PNP (10 nM) a G-protein activator alone (MacDonald et al, 2002; replicated the effect of Ex-4 whereas the GLP-1R antagonist exendin (9-39) (10-8M; MacDonald et al, 2002) failed to have an impact on the K v current, indicating a receptor specific effect. This effect is cAMP/PKAdependent as pre-treatment with the cAMP pathway antagonist Rp-cAMPS (100μM;MacDonald et al, 2002; or the PKA inhibitor H89 (1μM; reduced the effect of GLP-1R agonists on the K v current. GLP-1R-mediated antagonism of K v was found not to depend on Epac as inclusion of the Epac activator 8CPT-2Me-cAMP (50 μM) had no effect on the delayed-rectifying current .…”
Section: Potassium Channelsmentioning
confidence: 97%
See 1 more Smart Citation
“…Inclusion of the non-hydrolyzable GTP-analogue GMP-PNP (10 nM) a G-protein activator alone (MacDonald et al, 2002; replicated the effect of Ex-4 whereas the GLP-1R antagonist exendin (9-39) (10-8M; MacDonald et al, 2002) failed to have an impact on the K v current, indicating a receptor specific effect. This effect is cAMP/PKAdependent as pre-treatment with the cAMP pathway antagonist Rp-cAMPS (100μM;MacDonald et al, 2002; or the PKA inhibitor H89 (1μM; reduced the effect of GLP-1R agonists on the K v current. GLP-1R-mediated antagonism of K v was found not to depend on Epac as inclusion of the Epac activator 8CPT-2Me-cAMP (50 μM) had no effect on the delayed-rectifying current .…”
Section: Potassium Channelsmentioning
confidence: 97%
“…Patch-clamped experiments in rat islets have shown that GLP-1 (10 nM) and Ex-4 (10 nM) can antagonize K v currents (MacDonald et al, 2002). GLP-1 and Ex-4 treatment induces a 20 mV hyperpolarizing shift in the voltage dependence of steady-state activation of K v channels.…”
Section: Potassium Channelsmentioning
confidence: 99%
“…4), we hypothesised that the physiological secretagogue GLP-1 could regulate Kv channel function. Indeed, we have found that GLP-1 and the GLP-1 receptor agonist exendin 4 inhibit voltage-dependent outward K + currents in rat beta cells voltage-clamped in the whole-cell configuration by approximately 40% in a cAMP/PKA dependent manner and prolongs the time-course of beta-cell repolarisation following transient depolarisation by current injection [54].…”
Section: Regulation Of Kv Channel Activity In Beta Cellsmentioning
confidence: 99%
“…It is unlikely that this channel contributes to the insulinotropic effect of TEA however, since it is insensitive to the commonly used concentrations of this compound when applied extracellularly. Kv1.4, and possibly Kv4.2 [54], therefore could contribute to the TEA-insensitive inactivating current in rat beta cells, although the small amplitude of the inactivating currents observed [52] does not seem to reflect the abundance of these channels at the protein level [52,54]. As for the TEA-sensitive A-current detected in mouse beta cells [81] and mouse insulinoma cells [3], it seems likely that this current is mediated by Kv3.4, detected in mouse beta cells by immunohistochemistry [82], since this fast-inactivating Kv channel is sensitive to TEA.…”
Section: Electrophysiological Evidence For Different Repolarising Curmentioning
confidence: 99%
See 1 more Smart Citation